Investigation of cerebral venous outflow in microgravity. (31st October 2017) - Taibi, A; Gadda, G; Gambaccini, M; Menegatti, E; Sisini, F; Zamboni, P
Abstract: Objective : The gravitational gradient is the major component to face when considering the physiology of venous return, and there is a growing interest in understanding the mechanisms ensuring the heart filling, in the absence of gravity, for astronauts who perform long-term space missions. Approach : The purpose of the Drain Brain project was to monitor the cerebral venous outflow of a crew member during an experiment on the International Space Station (ISS), so as to study the compensatory mechanisms that facilitate this essential physiological action in subjects living in a microgravity environment. Such venous function has been characterized by means of a novel application of strain-gauge plethysmography which uses a capacitive sensor. Main results : In this contribution, preliminary results of our investigation have been presented. In particular, comparison of plethysmography data confirmed that long duration spaceflights lead to a redistribution of venous blood volume, and showed interesting differences in the amplitude of cardiac oscillations measured at the level of the neck veins. Significance : The success of the experiment has also demonstrated that thanks to its easy portability, non-invasiveness, and non-operator dependence, the proposed device can be considered as a novel tool for use aboard the ISS. Further trials are now under way to complete the investigation on the drainage function of the neck veins in microgravity.